Revelation of the Continents of Imagination. (29th October 2021) - Galovič, Roman
Abstract: It has long been argued that one of the main appeals of contemporary Euro‐American shamanism lies in its ability to reenchant the world in the disenchanted present. As observed during field research among shamans in the Czech Republic and based on an analysis of their techniques and discourse, the source of this reenchantment lies in journeys to non‐ordinary reality, internally experienced by participants during drumming. The reason those journeys are experienced as real is found in the autonomy of imagination, in images that come to mind spontaneously without participants' deliberate construction. The faculty of imagination provides a mechanism for the experience of a reenchanted world, whereas shamanic techniques and lectures on the nature of the world provide its emotional and cognitive contours. In ceremonial space, shamanic praxis then tunes a certain mode of being with its intertwined moments of corresponding understanding, attunement, and speech, such as those analyzed by Heidegger in Being and Time .